Influence of Biostimulant on Growth, Flowering and Yield of Summer Squash (Cucurbita pepo L.) Hybrids in Gangetic Plains of West Bengal - Chakraborty, Satadal; Karak, Chandan; Chakraborty, Biswajit; Marandi, Sanjita; Mollick, Sourav; Choudhuri, Partha; Thapa, Umesh; Thakur, Pran Krishna (International Journal of Bio-resource and Stress Management, 2026)
The experiment was undertaken during December, 2023–February, 2024 to evaluate the effect of different concentrations of the ECOHUME biostimulant on the vegetative growth, flowering, and yield of two different summer squash hybrids. The experiment was framed employing two-factorial Randomized Block Design (RBD) consisting five levels of treatments including untreated control and ECOHUME doses of 0.5, 1, 2, and 4 ml l-1 and two hybrids. Observations were recorded on key parameters of growth, flowering, yield and phytotoxicity effects on plants. Results revealed significant interactions between biostimulant doses and hybrids across most of the growth and yield parameters. ECOHUME at 2 ml l-1 (T4) was found to be the most effective dose, significantly enhancing plant height, number of leaves, number of male and female flowers, fruit length, diameter, average fruit weight, and total yield plant-1 and plot-1. Sunny house consistently outperformed Golden house in most of the parameters, indicating a stronger varietal response to the ECOHUME biostimulant. However, excessive application at 4 ml l-1 (T5) resulted in phytotoxic symptoms such as stunted growth, leaf burn, browning of flower buds, fruit necrosis and eventual crop failure. ECOHUME application at optimal concentrations improved vegetative growth and enhances reproductive efficiency as well as overall yield in compare to untreated control, demonstrating its potential as a sustainable input in integrated nutrient management in the Alluvial plains of West Bengal. The study underscored the importance of precised dose management to avoid toxicity and supported the role of biostimulant in enhancing crop performance, especially for high-value vegetable crops like summer squash in particular in the region.